TRANSFORMATION MODEL OF ENTREPRENEURIAL UNIVERSITY: AN ETHNOGRAPHIC APPROACH - Kurnia Endah Riana; Rini Dwiyani Hadiwidjaja; Yanuar Trisnowati; Pesi Suryani (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to develop a transformation model of the entrepreneurial university in Indonesia using an ethnographic approach. The research was conducted at five state universities with legal entity (PTN-BH) that have implemented institutional entrepreneurial initiatives. Data were collected through participant observation, in-depth interviews, and focus group discussions with key actors, including university leaders, lecturers, and business incubator managers. The findings reveal that the transformation process occurs in four key stages: initiation, experimentation, consolidation, and institutionalization. The success of this transformation is influenced by four main dimensions: strategic leadership, institutional structure, entrepreneurial culture, and actor dynamics. This study offers a theoretical contribution to understanding institutional change in developing countries and a practical framework for higher education policymakers. The ethnographic approach enables a deep exploration of the social and cultural dynamics underpinning institutional transformation in universities.